SiMCaPe - Sistema para a montagem de cariótipo de peixe baseado em conjuntos difusos - Faria, Elaine Ribeiro de (2006)
The karyotype study of several organisms has a its objective to observe numerical variations, for detecting specific characteristics and to study the evolution of the species. Manual assembling of karyotype is a repetitive, subjective and time consuming task. This project describes the SiMCaPe, an interactive system for assisting the assembling of fish karyotype from digitized photomicrography of fish cells in metaphase. The SiMCaPe has 5 modules: pre-processing and segmentation, rotation, centromere location, classification and pairing. To pre-process and segment the chromosomes, methods based on fuzzy sets were used. To rotate the chromosome to its vertical position, the orientation of the central axis of the chromosome skeleton was used. To locate the centromere, a horizontal projection vector of the chromosome was used. To classify the chromosomes in metacentric, submetacentric, subtelocentric and acrocentric classes, a fuzzy inference system, which combines rules including feature descriptors as the centromeric index and the ration between the longer and shorter arms, was used. The pairing of the chromosomes was made according to the chromosomes size. The proposed methods were applied to 5 species of fish: Astyanax altiparanae, Astyanax eigenmanniorum, Astyanax scabripinnis, Hoplias malabaricus e Hoplias lacerdade. The tests were carried out using 40 images, which contained on average 49.2 chromosomes in each image. In the segmentation process, on average 64.05% of the chromosomes in each image were separated correctly, in the rotation process, on average 69.05% of the chromosomes in each image were rotated correctly. The results obtained by the SiMCaPe system for the centromere location and classification process were compared with the results obtained by two groups of cytogeneticists. Comparing the results of the system with the first group of cytogeneticists, the level of agreement between the tow for the centromere location was 71.95% and for the classification 78.52%. Comparing the results of the system with the second group, the level of agreement between the two for the centromere location was 78.83% and for the classification 81.16%.